2015
DOI: 10.1016/j.ajpath.2015.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Podocyte Injury–Driven Lipid Peroxidation Accelerates the Infiltration of Glomerular Foam Cells in Focal Segmental Glomerulosclerosis

Abstract: Intracapillary foam cell infiltration with podocyte alterations is a characteristic pathology of focal segmental glomerulosclerosis (FSGS). We investigated the possible role of podocyte injury in glomerular macrophage and foam cell infiltration in a podocyte-selective injury model (NEP25 mice) and hypercholesterolemic model [low-density lipoprotein receptor deficiency (LDLR(-/-)) mice] with doxorubicin-induced nephropathy. Acute podocyte selective injury alone failed to induce glomerular macrophages in the NEP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 56 publications
0
40
0
Order By: Relevance
“…8 In a series of Miniature Schnauzer dogs, hyperlipidemia was associated with the presence of glomerular foam cells (observed with TEM), but glomerular lipid thromboemboli were more common than were dilated loops filled with foam cells. 5 Further studies are required to determine the association between hyperlipidemia and glomerular foam cell accumulation in dogs.…”
Section: Discussionmentioning
confidence: 99%
“…8 In a series of Miniature Schnauzer dogs, hyperlipidemia was associated with the presence of glomerular foam cells (observed with TEM), but glomerular lipid thromboemboli were more common than were dilated loops filled with foam cells. 5 Further studies are required to determine the association between hyperlipidemia and glomerular foam cell accumulation in dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the importance of the inflammatory milieu in the foam cell formation [91,134,135]. Cytokines such as TNFα and IL-1β can modify LDL receptor-mediated…”
Section: The Fatty Kidney In Dnmentioning
confidence: 99%
“…Increased podocyte detachment has been observed in patients with obesity related-glomerulopathy, focal segmental glomerulosclerosis (FSGS), and DN [90]. In this regard, podocytopenia could be mediated by alterations in the lipid balance [90,91].…”
Section: Lipotoxicity In Renal Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…We speculate that increased PLA2 activity in damaged podocytes and/or tubular epithelial cells may cause higher urinary concentrations of LPC and FA. Recently, a mouse model of FSGS induced by podocyte-specific injury of a double transgenic mouse (NEP25/LDLR-/-) with severe hypercholesterolemia displayed glomerular lipid peroxidation, foam-cell formation, and glomerular accumulation of LPC [31]. …”
Section: Discussionmentioning
confidence: 99%